2019
DOI: 10.1016/j.dib.2018.11.133
|View full text |Cite
|
Sign up to set email alerts
|

Dataset on the nurses’ knowledge, attitude and practice towards palliative care

Abstract: When a patient enters the end stage of life threatening disease like cancer, treatment of pain and other symptoms must be considered to preserve quality of life (Gielen et al., 2011) [1]. Nurses have an important role in the care of patients who suffered from life threatening diseases. End of life cares is one of the routine activities of nurses (Gott et al., 2012) [2]. We surveyed knowledge, attitude and practice of nurses who worked in the hospitals of Neyshabur University of Medical Sciences towards palliat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
27
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 5 publications
5
27
1
Order By: Relevance
“…Nurses' palliative care mean total knowledge score (9.34) appears to be deficient in this study. This finding is higher compared to the previous studies undertaken in Saudi Arabia (2009), Southeast Iran (2014), and Iran (2019) [20][21][22]. Meanwhile, our study result is lower matched to researches reported from Canada (2009), in the USA [2009], Australia (2008) and Ireland (2016) [17,[30][31][32].…”
Section: Discussioncontrasting
confidence: 95%
See 4 more Smart Citations
“…Nurses' palliative care mean total knowledge score (9.34) appears to be deficient in this study. This finding is higher compared to the previous studies undertaken in Saudi Arabia (2009), Southeast Iran (2014), and Iran (2019) [20][21][22]. Meanwhile, our study result is lower matched to researches reported from Canada (2009), in the USA [2009], Australia (2008) and Ireland (2016) [17,[30][31][32].…”
Section: Discussioncontrasting
confidence: 95%
“…Our analysis displayed level of hospitals, education qualification and clinical working units has no significant association with the nurses' attitude toward end-of-life care. However, a higher level of education, working in a medical ward, and nurses received training on PC showed a more favorable attitude towards PC [17,19,22]. The experience of nurses and attitude toward end-of-life care is incongruent to each other in this study which might be affected by nurses' belief (religion and culture), their compassion and experience adapted from family members.…”
Section: Plos Onementioning
confidence: 57%
See 3 more Smart Citations